MAQASHID SYARI’AH AS A FILTER OF HOAX THROUGH AL-QURAN PERSPECTIVE - Doli Witro (IAIN Manado, 2020)
A report of the information from non-profit organization, Communication and Broadcasting Technology, namely the Indonesian Telematics Society (Mastel) in 2019, are based on the results of a survey. It is conducted with 34.60% respondents who receive hoax news every day. Not only to ordinary people, but hoaxes also has come to the educated circles. In Islamic shari'ah, all aspects of life are regulated based on the Al-Quran and Sunnah so that it creates benefit for its adherents and cannot be separated in delivering and receiving the news. Speaking through the benefits, it seems that, it has referred to the purpose of Islamic shari'ah, in which the language of religion is called maqashid syari'ah. This paper focuses on the hoax phenomenon on social media using maqashid syari'ah. This paper aims to further examine the maqashid syari'ah as a news filter on the internet. This study employs a qualitative research type of library research. The data obtained from books, journals, and articles related to maqashid syari'ah and hoaxes. After the data were obtained, the data were presented in a descriptive narrative and were analyzed by using analysis techniques, namely data reduction, data presentation, and data verification. The results show that the five divisions of maqashid syari'ah are able to answer religious previous and contemporary problems of hoaxes. Meanwhile, Maqashid syari'ah can be employed as a filter for every news broadcasted and accepted by the community.